2013
DOI: 10.1364/ol.38.004813
|View full text |Cite
|
Sign up to set email alerts
|

Phase retrieval from one partial derivative

Abstract: Phase objects can be characterized using well-known methods such as shear interferometry and deflectometry, which provide information on the partial derivatives of the phase. It is often believed that for phase retrieval it is strictly necessary to have knowledge of two partial derivatives in orthogonal directions. In the praxis, this implies that the measurements have to be performed along two dimensions, which often requires a rotation of the object or rotation of the shear direction. This is time consuming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…(8) or Eq. (9) (see, e.g., [27,28]). However, when the measured intensity distributions I k x; y are degraded by noise, a situation that takes place invariably in laboratory and field applications, the integration along a single coordinate produces poor-quality results.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…(8) or Eq. (9) (see, e.g., [27,28]). However, when the measured intensity distributions I k x; y are degraded by noise, a situation that takes place invariably in laboratory and field applications, the integration along a single coordinate produces poor-quality results.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…where α (0 ≤ α ≤ 1) is a filtering parameter that eliminates the high spatial frequency [20]. This method was employed for the streak-noise-free PC imaging with SIXM.…”
Section: Figure 2 Schematic Drawing Of 1d Diffuser (Left) and Its Phmentioning
confidence: 99%
“…(6) and to retrieve the absolute value of the phase delay. However, a simple homogeneous Dirichlet condition of zero phase delay at image boundaries (suggested, for instance, in [13]) is a rarely encountered condition in practice. It is often impossible to isolate an object in the center of the camera field of view so that it is surrounded by air, where X-ray phase remains unperturbed.…”
Section: Phase-retrieval Boundary Value Problem and A Priori Informationmentioning
confidence: 99%
“…It was also shown that the basic phase retrieval problem can be converted to an elliptic partial differential equation [13,14]. In this work we explore this approach in details.…”
Section: Introductionmentioning
confidence: 99%